2008
DOI: 10.1002/hyp.7154
|View full text |Cite
|
Sign up to set email alerts
|

Consistency between hydrological models and field observations: linking processes at the hillslope scale to hydrological responses at the watershed scale

Abstract: Abstract:The purpose of this paper is to identify simple connections between observations of hydrological processes at the hillslope scale and observations of the response of watersheds following rainfall, with a view to building a parsimonious model of catchment processes. The focus is on the well-studied Panola Mountain Research Watershed (PMRW), Georgia, USA. Recession analysis of discharge Q shows that while the relationship between dQ/dt and Q is approximately consistent with a linear reservoir for the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
266
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(280 citation statements)
references
References 43 publications
(75 reference statements)
11
266
1
Order By: Relevance
“…This scatter reduction in recession plots might improve model fit and has been applied in a number of studies (e.g. Clark et al, 2009;Palmroth et al, 2010;Ajami et al, 2011;Staudinger et al, 2011).…”
Section: Roles Of Extraction Procedures and Parameterization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This scatter reduction in recession plots might improve model fit and has been applied in a number of studies (e.g. Clark et al, 2009;Palmroth et al, 2010;Ajami et al, 2011;Staudinger et al, 2011).…”
Section: Roles Of Extraction Procedures and Parameterization Methodsmentioning
confidence: 99%
“…Beyond that, RAMs are often used to estimate recession behavior over different scales (e.g. hillslopes, catchment size) (Clark et al, 2009;Wang, 2011) or to characterize storage capacity (Sayama et al, 2011) or recession timescales (Aksoy and Wittenberg, 2011;Krakauer and Temimi, 2011). In these applications, the choice of RAM will directly influence the estimated properties of water availability.…”
Section: The Effect Of Different Rams To Distinguish Catchments' Recementioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate and multiscale diagnostic metrics of model behavior should provide insight into both the individual processes within a model as well as how interlinked processes combine to produce the system-scale response at larger spatial scales Luo et al, 2012]. For example, analysis of recession behavior can provide more information on model weaknesses than analysis of summary metrics of model performance such as the Nash-Sutcliffe score [Yilmaz et al, 2008;Clark et al, 2009]. Essentially, models need to reproduce both realistic temporal hydrologic behavior (i.e., high frequency and low frequency) and realistic spatial patterns of variability across a hierarchy of scales.…”
Section: Process-based Model Evaluationmentioning
confidence: 99%
“…Several studies also illustrated the non-uniqueness of the response of discharge to storage. For instance, Clark et al (2009) illustrated for a mountain watershed in Georgia (USA) that the recession relationships of (dQ/dt) and Q is approximately consistent with a linear reservoir at a hillslope scale and deviation from linearity becomes progressively larger with increasing spatial scale, and MyrabĂž (1997), Beven (2006), Ewen and Birkinshaw (2007), Spence et al (2010), Martina et al (2011) and Fovet et al (2015 reported hysteresis in discharge-storage relationships. Furthermore, Teuling et al…”
mentioning
confidence: 99%